Unfinished Business: Performative Interviews as a Method for Expressing Failure in the Socially Engaged Art Job - Hope, Sophie (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Socially engaged art has, for some, become a professionalised, freelance funded form of labour. It is work that involves emotional labour, empathy and compassion, demonstrated by the trust that is often needed between (paid) artists and (unpaid) participants in order for projects to develop. In order to preserve the already precarious funding of this industry there is a tendency to promote the positive and successful aspects of these projects. This article explores how the imperative to present the work in a positive light has led to a culture of silence and individualised absorption of failure when things start to go wrong. Through a re-examination of a series of Performative Interviews, the article reflects on this playful method for speaking out about unfinished, cancelled or compromised socially engaged art jobs. In doing so, the theatrical frameworks of both the socially engaged art job and research interview are brought into focus.